2004
DOI: 10.1016/j.ehj.2004.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Changes in autonomic nervous system activity: spontaneous versus balloon-induced myocardial ischaemia

Abstract: Balloon inflation and occlusion evokes baroreceptor vagal predominance in response to a stretch stimulus of the coronary artery. Conversely, spontaneous occlusion during unstable angina is accompanied by naturally occurring sympathetic activation. Sympathetic activation may have a role in the natural history of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 39 publications
0
24
0
2
Order By: Relevance
“…Sympathetic nervous system activation and norepinephrine release [3], concomitant with the release of natriuretic peptides [4] occur after myocardial injury and during the development of adverse left ventricular (LV) remodeling. Interestingly, these molecules are also major contributors to the growth and stimulation of brown adipose tissue (BAT) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Sympathetic nervous system activation and norepinephrine release [3], concomitant with the release of natriuretic peptides [4] occur after myocardial injury and during the development of adverse left ventricular (LV) remodeling. Interestingly, these molecules are also major contributors to the growth and stimulation of brown adipose tissue (BAT) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It could be associated to sympathovagal balance of the ANS towards either a sympathetic or parasympathetic prevalence, and may represent a beneficial adaptive mechanism for increasing coronary flow during myocardial ischemia. There are evidence that balloon inflation and occlusion evokes baroreceptor vagal predominance in response to stretch stimulus of the coronary artery [16].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies with a human angioplasty model focused on an analysis of heart rate variability [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Manfrini et al [17] have shown that balloon inflation decreases low frequency fluctuation of RR variability, and suggested that coronary occlusion results in sympathetic withdrawal. Studies based on heart rate variability assume that this method measures sympathetic and vagal tone and its balance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation